Penerapan Nilai-Nilai Pendidikan Multikultural Untuk Mencegah Bullying di MAN 2 Model Medan - Ritonga, Dedi Prima; Ananda, Rizki; Dalimunthe, Putri Ani (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Bullying is a phenomenon that occurs in many educational institutions, including MAN 2 Model Medan School. The most common factors that cause this in students are family factors, peer factors, and seniority factors. The purpose of this study is to reduce bullying behavior in MAN 2 Model Medan; therefore, this study describes the implementation of multicultural education values applied in MAN 2 Model Medan. This study uses a qualitative research method, which does not include statistics in qualitative research analysis and is limited to descriptive explanations. Data sources in this study are divided into two types of sources: primary data sources (incidents that are converted into data by field-based experimental data researchers) and secondary data (case reports of children from BK teachers and student organizations at the research location). Observations, interviews, and documentation studies are used as data collection tools. Based on the results of the author's research, the implementation of effective multicultural education in MAN 2 Model Medan is indicated by the very few incidents of bullying between students and students. Teachers at MAN 2 Model Medan School have implemented multicultural education values by teaching about cultural diversity through a cultural assimilation approach, prioritizing the values of peace, brotherhood, equality, justice, tolerance, and guidance. Students also learn to think about diversity to strengthen different approaches to social relations, pluralism, diversity, and equality without discrimination between social classes